Pengaruh Karakteristik Kewirausahawan Terhadap Kerberhasilan Sebuah Usaha - Sinta Affrilliana Sari; Mutiara Azahra Sinaga; Rhea Aquila Fawas; Mansur Keling (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research was conducted with the aim of identifying and analyzing the impact and influence of entrepreneurial characteristics on business success. The data analysis method used is a qualitative research method based on library research. The data analysis technique used analyzes the content of information collected and taken from various sources and references related to the research title. The personality traits of an entrepreneur have a significant influence on the success of the company. Entrepreneurial qualities are an important and inseparable part of becoming an entrepreneur. Because a positive personality makes it easier to face and overcome any situation.